Winning strategies for successful aging - Pfeiffer, Eric, 1935- (Yale University Press health & wellness., 2013)
For anyone who is approaching a 65th birthday with trepidation, this valuable book offers heartening advice on navigating the later years of life. Dr. Eric Pfeiffer, who for thirty years has cared for--and learned from--elderly people, addresses with compassion and deep understanding the multitude of issues that arise for aging individuals and their families. He writes authoritatively but in a conversational tone. His advice is easy to read, easy to follow, and full of wisdom. In short, practical chapters, Dr. Pfeiffer advises on choosing an ideal place to live, finding a range of satisfying activities, and maintaining an active social life. He also explains how best to maintain one's health, mental health, wealth, and independence. Other chapters explore the importance of a spiritual life and the value of maintaining an active sexual life. In addition, the author speaks to the value of charitable giving and describes how it is possible to prepare for a good good-bye to life. Filled with illustrative anecdotes and enhanced with a lovely selection of poems, this reassuring book demonstrates how it is possible to direct and control the aging experience. For every person approaching retirement years, and for their friends and families, the book is an excellent resource and a practical guide.